Open price term under the United Kingdom Sale of Goods Act 1979 - Akrami, Farzaneh; Sakina Shaik Ahmad Yusoff,; Suzanna Mohamed Isa, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In the contemporary world, man is witnessing the advancement of science and technology that has led to considerable changes in all areas of human life and in the definition of many concepts. In such a dynamic world, each science should do its part in coordinating with these developments in a manner that does not make any of the aspects of life to be imperfect or disturbed. ‘Law’ also has certain responsibilities among which the incontrovertible task to update old and insufficient rules. Choosing the subject of 'open price in sale of goods contracts', this article aims to study imperfect and old regulations on this issue in the United Kingdom Sale of Goods Act 1979 and suggest certain amendments through which the amount of the problematic consequences of such rules is expected to decrease. This study is a result of a doctrinal research with a library-based data collection method.